Using Design Research for Studies on ICT in Classrooms - Hyeran Park; Zuochen Zhang (University of Windsor, 2011)
In recent years, as Information and communication technologies (ICT) are getting more and more widely used in classrooms, researchers have been trying to identify effective ways for ICT to be utilized in school classrooms to enhance teaching and learning. However, it is argued that traditional scientific research methodologies are not really applicable for studies on ICT integration in classrooms, as these research approaches, more often than not, fail to reflect the dynamics and complexity of the school classroom. Some researchers who adopted design research in their research projects advocate the employment of this research methodology as an alternative to overcome the limitations of traditional scientific research in the domain of ICT integration in classrooms. Based on a review of literature, this paper first examines the advantages and problems of adopting ICT in classrooms, and then discusses the use of design research as an alternative research methodology for studies on ICT in classrooms.